Defect‐Passivating and Stable Benzothiophene‐Based Self‐Assembled Monolayer for High‐Performance Inverted Perovskite Solar Cells - Liu, Ming; Li, Mingliang; Li, Yanxun; An, Yidan; Yao, Zefan; Fan, Baobing; Qi, Feng; Liu, Kaikai; Yip, Hin‐Lap; Lin, Francis R.; Jen, Alex K.‐Y. (Advanced energy materials, 2024)
Effective passivation of defects at the buried interface between the perovskite absorber and hole‐selective layer (HSL) is crucial for achieving high performance in inverted perovskite solar cells (PSCs). Additionally, the HSL needs to possess compact molecular packing and intrinsic photo‐ and thermo‐stability to ensure long‐term operation of the devices. In this study, a novel MeO‐BTBT‐based self‐assembled monolayer (SAM) is reported to serve as an efficient HSL in inverted PSCs. Compared to the well‐established carbazole‐containing SAM MeO‐2PACz, MeO‐BTBT has flat and more extended conjugation with large atomic radius of the sulfur atom. These induce stronger intermolecular interactions to enable more ordered and compact SAM to be formed on indium–tin oxide (ITO) substrates. Meanwhile, the sulfur atoms in MeO‐BTBT can coordinate with Pb2+ ions to passivate the defects at the buried interface of perovskite absorber. The derived perovskite films show both high photoluminescence (PL) quantum yield (13.2%) and a long lifetime (7.2 µs). The PSCs based on MeO‐BTBT show a PCE of 24.53% with an impressive fill factor of 85.3%. The PCEs of MeO‐BTBT‐based devices can maintain ≈95% of their initial values after being aged at 65 °C for more than 1000 h or continuous operation under 1‐sun illumination. A benzothiophene‐based SAM HSLMeO‐BTBT is developed. Compared to the carbazole‐based MeO‐2PACz SAM, MeO‐BTBT shows stronger intermolecular interactions, a passivation effect at the buried interface, and better photo‐stability, enabling a robust HSL and stable perovskite bottom interface morphology. The devices with the MeO‐BTBT HSL achieves a PCE of 24.53% with excellent long‐term device stability under illumination and thermal stress.